Tumor-associated neutrophils display a distinct N1 profile following TGFβ modulation: A transcriptomics analysis of pro- vs. antitumor TANs - Shaul, Merav E.; Levy, Liran; Sun, Jing; Mishalian, Inbal; Singhal, Sunil; Kapoor, Veena; Horng, Wenhwai; Fridlender, Gil; Albelda, Steven M.; Fridlender, Zvi G. (Oncoimmunology, 2016)
It is becoming increasingly clear that tumor-associated neutrophils (TANs) play an important role in cancer biology, through direct impact on tumor growth and by recruitment of other cells types into the tumor. The function of neutrophils in cancer has been the subject of seemingly contradicting reports, pointing toward a dual role played by TANs in tumor progression. The existence of multiple neutrophil subsets, as well as phenotypic modulation of the neutrophils by various factors in the tumor microenvironment, has been shown. TGFβ plays a significant role in the determination of neutrophils' phenotype, by shifting the balance from an antitumor (N1) toward a more permissive (N2) phenotype. The full range of mechanisms responsible for the pro- vs. antitumor effects of TANs has not yet been elucidated. Therefore, the ability to identify the different neutrophil subpopulations in the tumor is critical in order to understand TANs evolution and contribution throughout tumor progression. Using a transcriptomic approach, we identified alternations in gene expression profile following TGFβ inhibition. We show that N1 and N2 TANs represent distinct subpopulations with different transcriptional signatures and both differ from naive bone marrow neutrophils. The analysis highlights a clear difference in pathways involved in neutrophil function such as cytoskeletal organization and antigen presentation, as well as alterations in chemokine profile, eventually affecting their effect on tumor cells and tumor growth. These data highlights several potential new pathways and mechanisms by which neutrophils can influence both the tumor cells and the adaptive immune system.